Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.